Pengaruh Minat Membaca dan Motivasi Belajar Terhadap Prestasi Belajar IPA Siswa - Retariandalas Retariandalas (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
This research aimed to determine the influences of variables of reading interest and learning motivation against students natural sciences achievement. The Research used a survey method with 100 sample students which taken by random sampling among the 8th-grade junior high school students in Sukmajaya district, Depok regency. Data collected with questionnaires that had been validated. The Research used multiple regression paradigms. The data were analyzed with statistic description and hypotheses test and also requirement data tests including normality test, linearity test, multicollinearity test and heteroscedasticity test. The results of the research were: 1) reading interest and learning motivation were together significantly influenced students natural sciences achievement, 2) reading interest was not significantly influenced students sciences achievement 3) learning motivation was significantly influenced students sciences achievement.